35O Phase I clinical trial of PD-1 knockout anti-MUC1 CAR-T cells in the treatment of patients with non-small cell lung cancer. (15th December 2019) - Lin, Y; Chen, S; Zhong, S; An, H; Yin, H; McGowan, E
Abstract: Background: Little has been done on assessing the safety and efficacy of programmed death-1 (PD-1) knockout (KO) engineered CART cells in cancer patients. Here we designed a clinical trial to evaluate the safety of PD-1 KO engineered anti-MUC1 CART cells for the treatment of patients with advanced non-small cell lung cancer (NSCLC). The primary endpoint was to evaluate the safety of the new treatment. Methods: Patients (age ≥ 18) were recruited according to the criteria in NCT03525782. MUC1-specific CARs were constructed using the SM3 scFv. Following lenti-MUC1 CAR retroviral transduction, efficiency of transgenic expression was assessed by flow cytometry. PD-1 gene KO in the CAR positive T cells was achieved using the CRISPR-Cas9 system and validated by sequencing and flow cytometry. MUC1-CAR+/PD-1- T cells at a starting dose of 2.5x10 6 /KG were infused over 60 mins. Following treatment, patients' general condition, levels of lymphocytes, IL-6, hs-CRP, PCT, CYFRA21, NSE(E), and SCC were monitored. Circulating CART cells were checked regularly. Changes in tumor size were examined by MRI scans. Results: Up to the study cutoff date, 19/9/2019, 20 patients diagnosed with NSCLC (IIIb to IV), were recruited. All participants received at least one cycle of anti-MUC1 CART cell treatment. Among the 20 treated patients, 8 received 1 cycle, 9 received 2 cycles, 2 received 3 cycles, and 1 received 4 cycles. Common adverse events (AEs) were acute fever (3 pts, 38.2-39.8 C ◦ ), chills (2 pts), headache (1 pt), skin rash (1 pt), diarrhea (1 pt), and nausea & vomiting (1 pt). No grade 3-5 AEs and CRS was observed. Of the 20 assessed patients, 11 presented with stable disease while 9 had progressive disease. All patients had significant symptom improvements after infusion. Circulating CART cells gradually declined after infusion and the number dropped down to approximately 20% in 4 months after one cycle treatment, indicating the necessity of further cycles. Conclusion: Our data suggests that the treatment with PD-1 disrupted anti- MUC1-CAR cells is safe and well tolerated by all NSCLC patients. Importantly no CRS was indicated in all cases. The efficacy of this unique combined therapy was still inconclusive and will be explored in our next phase study. Clinical trial identification: NCT03525782. Legal entity responsible for the study: Guangzhou Anjie Biomedical Technology Co. Ltd. Funding: Guangzhou Anjie Biomedical Technology Co. Ltd. Disclosure: All authors have declared no conflicts of interest.